Konsep Mahar Pekawinan dalam Fiqh Kontemporer Analisis Mubadalah - Harsya, Rabith Madah Khulaili; Rohmah, Umdah Aulia (Fakultas Syariah INSURI Ponorogo, 2022)
The concept of a marriage dowry from various time formalities considers the sale and purchase transaction, that is, the sale and purchase between the future husband who is the buyer and the father or brother on the basis that the future wife is their material right. At first the guardian i.e. father or grandfather and close relatives who cared for the woman considered the dowry to be their right in exchange for the obligation to care for and nurture the woman. This understanding makes for a sociological reality in Muslim society that exposes women to discrimination, exploitation and violence. Ironically, almost all such destructive treatment is justified by religion. Women are not recognized as fully human like men, so they have no right to represent themselves. Women have always been regarded as objects of law in all laws and regulations, especially those relating to family law. In contemporary fiqh, dowry is defined as the obligatory gift of a man to a woman in the presence of a marriage contract, it is a good protection of Islam and its respect for women is that Islam gives her the right of ownership. The obligation of dowry in the Qur'an in sura an-Nisa verse 4 The imposition of only one subject results in the reading of the text in a patriakhis manner that is not in harmony with Islamic principles. In Islam a text is not specific to gender as the command of prayer, zakat, fasting of course although the editors of mukhatab are men but also target women. Contemporary fiqh does not apply the size of the dowry, meaning that the dowry can be expensive or cheap depending on the situation and the place that occurs. The understanding that requires a dowry on the part of the husband (man) alone is not in harmony with the principle of mubadalah. The reason is because according to mubadalah every sacred text whose mukhotob is male then it can certainly be applied to women. Likewise, with the obligation to give a dowry by men, it can also be from the side of the woman who gives the dowry